Persepsi masyarakat tentang perubahan sosial-ekonomi penyebaran limbah PLTU Bolok terhadap kegiatan budidaya rumput laut di Perairan Kecamatan Kupang Barat - Conceicao, Julio Danilson Da; Sunadji, Sunadji; Ratoe Oedjoe, Marcelien Dj (Nusa Cendana University, 2023)
This research aims to determine socio-economic perceptions before and after the distribution of Bolok PLTU waste towards seaweed cultivation activities, carried out for 1 month in Kuanheum and Oenaek waters, West Kupang District. Data collection was carried out randomly from 30 respondents in both villages. The results of this research show that the distribution of PLTU Bolok waste has an impact on the socio-economic life of seaweed cultivators. This can be seen from the results of the Paired sample T-test showing a significance value of 0.000 < the 2 tailed significance value of 0.05, which means H0 is rejected and H1 is accepted. Where after social life waste such as cooperative interactions decreased to 63.3%, competition increased to 40%. Conflict increased by 33.45%, the number of cultivators decreased by 96.7%, population migration increased to 30% and farmers switching jobs decreased to 53.4% and children dropping out of school decreased by 10%. Meanwhile, after the waste of economic life, such as the use of personal capital decreased by 50%, loan funds increased by 50%, the use of ropes decreased by 100%, seaweed production decreased by 90%, and income decreased by 100%, production turnover decreased by 83.4% and additional farmer employment decreased by 53.3%